Wage policies in the public sector during wholesale privatization - Jelena Nikolic (IZA World of Labor, 2017)
Examining the implications of changes in public sector wage-setting arrangements due to privatization is a relatively new area of economics research, with few studies having analyzed the effects of public sector restructuring on relative wages in developed countries. There is, however, a growing empirical literature that measures the effects of transitioning from central planning to market-based systems on public–private sector wage differentials. Policymakers can learn from this evidence about the ways in which ownership transformation affects the distribution of wages in both the public and private employment sectors.
Keywords: J31; J42; J45; O17; P31; 330; public sector; wage compression; economic transition; wage policies